Treatment of allograft renal cell carcinoma with partial nephrectomy in a pediatric kidney transplant - Marina M. Tabbara; Mohamad Ammar Al Nuss; Jayanthi J. Chandar; Warren Alperstein; Gaetano Ciancio (Elsevier, 2021)
Renal cell carcinoma (RCC) is a common malignancy among kidney transplant recipients that often occurs in the native kidney. The incidence of RCC in the renal allograft is rare and carries the double risk of returning to dialysis and the development of metastatic cancer. The majority of reported cases of RCC in transplanted kidneys are in adult recipients and its occurrence in the pediatric age group is an uncommon event. There are currently no established guidelines on the treatment of RCC in transplant recipients.We report our experience of a 15-year-old male who developed allograft RCC 12 years later after transplantation. MRI confirmed the presence of the mass near the hilum of the renal allograft and biopsy revealed a Papillary Renal Cell Carcinoma (PRCC) type I. A partial allograft nephrectomy was successfully performed with negative tumor margins. The patient's serum creatinine 12 months post-operation was 1.9 mg/dL and presently he has no evidence of residual disease, recurrence, or metastasis.Partial nephrectomy is an effective treatment option for renal allograft RCC as it spares the patient from returning to dialysis until retransplantation is possible and necessary.